Trazos de economía nueva - Armando P. Spinelli (Económica, 1956)
To assure its stability the western World requires a doctrinarian and historical reconsideration of its socio-economic institutions. A possibility would be to amplify the power of administration to direct economic life within a democratic institutional framework. The realization of this possibility is hindered by the class struggles and the capitalistic forces. The first obstacle could be neutralized by means of doctrinarian and constitutional State interventions. As for the second, a transformation can be observed both in its ideological aspects and its material structure, caused by internal and external impulses. The profit principle is being replaced by the security idea and the impersonalization of enterprise converts management in wage earners which, fearing competition sign interenterpreneurial agreements. In order to overcome these obstacles and facing the danger of possible accumulation, stagnation and destruction of economic activity, the State intervention is fully justified. Although the classical economics keeps itself aloof from any ethical value judgment the mere fact that it is based on a free profit economy makes that its alleged neutrality must be taken with serious reservations. The theory must not only interpret reality but must also create the necessary tools for directing economic life, as its aims are evidently social.